مضادات الاكسده الانزيميه لمتلازمة اجهاد التاكسد عند مرضى ارتفاع ضغط الدم - ستار, سيران (University of Thi-Qar Journal of Science, 2008)
This study was designed to investigate the effect of the hypertensionduration on the enzymatic antioxidants (SOD,Catalase) in hypertensivepatients .The study was performed on 85 hypertensive patients (38 male,47 female ),compared to 75 healthy subjects (37 male ,38 female )wereinvestigated as a control group .The study showed a significant increase in specific activity ofantioxidant enzymes ;SOD and catalase compared to healthy subjects.While there was a significant decrease in specific activity of these enzymes as the hypertension duration increased .A positive correlation between SOD activity and atherogenic index was also shown .